2014
DOI: 10.14687/ijhs.v11i2.2791
|View full text |Cite
|
Sign up to set email alerts
|

Functionalist perspective on deviance

Abstract: This paper focuses on and summarizes the functionalist perspective of deviance, the function of crimes, and how these perspectives have influenced the development of Durkheim's work, anomie, for example. In this regard, our aim is to carefully describe the contributions of important functionalist thinkers such as Emile Durkheim and Robert K. Merton, by providing a brief historical discussion that highlights their contributions to deviance and crime research. Further, we are also primarily interested in how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…In understanding the pressures and opportunities presented by middle managers' work, we found that their position gave them sufficient agency to reach their goals, but only if they resorted to reinterpreting, appropriating, or thwarting established norms. Such findings illustrate how strain theories allow the re-insertion of the micro-perspective in how structure is enacted (see Ziyanak and Williams, 2014), a macro-micro bridging motivation that was core to Merton's (1968) theory.…”
Section: Contributions To Understanding Deviance In Middle Managementmentioning
confidence: 75%
See 1 more Smart Citation
“…In understanding the pressures and opportunities presented by middle managers' work, we found that their position gave them sufficient agency to reach their goals, but only if they resorted to reinterpreting, appropriating, or thwarting established norms. Such findings illustrate how strain theories allow the re-insertion of the micro-perspective in how structure is enacted (see Ziyanak and Williams, 2014), a macro-micro bridging motivation that was core to Merton's (1968) theory.…”
Section: Contributions To Understanding Deviance In Middle Managementmentioning
confidence: 75%
“…In these debates, the positive-negative dichotomy returned through the question of whether deviance aimed at achieving social goals (by unsanctioned means) or at escaping the contradictions of impossible situations (Agnew, 1985(Agnew, , 2012. However, as several scholars note, these arguments over operationalization and predictive validity largely left the underlying structure of the theory intact (Featherstone and Deflem, 2003;Ziyanak and Williams, 2014). More generally, structural theories have been critiqued for their tendency to see social orders as unified, totalized and static (e.g., Blumer, 1954;Burawoy, 1982).…”
Section: Deviance As a Response To Structural Strainmentioning
confidence: 99%